Pengembangan Panduan Keterampilan Proses Tema Daerahku dan Keindahan Alamnya Berbasis Kearifan Lokal Pada Guru SD di Blitar - Zainuddin, Mohammad; Surayanah, Surayanah; Lestariningsih, Lestariningsih (Universitas Nahdlatul Ulama Blitar, 2024)
The aim of the research that has been carried out is to produce a process skills book that is valid according to experts. This process skills book contains the theme of my region and its natural beauty. It is hoped that this book can be used by teachers in teaching and learning activities at school. This research was motivated by the need for material based on local Blitar wisdom in schools. This research was conducted on elementary school teachers in Blitar City using purposive sampling techniques. The research method used in this research is development research (Research and Developmnet) with a 4-stage (4-D) design modified to 3-D. The development model used is the Analyze, Design, Develop, Implementation and Evaluation (ADDIE) model. The research results show that the average validation result for media experts is 4.8 (good), material experts 4.6 (good) and users, namely teachers, 4.4 (good). With the socialization of the development of process skills guides based on local wisdom in Blitar, teacher knowledge increased by 55%.